The Effect of Work Motivation on Improving the Performance of Employees in the Water Hyacinth Craft Business in Aer Village, Palembang City - Anggraini, Puspita; Harahap, Lily Rahmawati; Effendi, RY.; Yani, Ria Astri (Universitas Dehasen Bengkulu, 2025)
The purpose of this study is to analyze the relationship between work motivation (X) and employee performance (Y) in the eceng gondok business. A simple linear regression analysis was used to determine the extent to which work motivation affects employee performance. The results show that work motivation significantly influences employee performance, with a regression coefficient of 1.379, a t-value of 4.527, and a significance value of 0.000, indicating a strong and significant relationship. The correlation coefficient (R) of 0.564 indicates a positive relationship between the two variables, while the R-squared value of 0.318 shows that work motivation accounts for 31.8% of the variation in employee performance. This study also found no signs of heteroscedasticity and meets the classical assumptions, making the regression model suitable and valid for explaining the relationship between work motivation and employee performance.